Size-controlled cobalt ferrite nanocrystals: magnetically separable reusable nanocatalysts for selective oxidation of styrene - Jeyavani, Vijayakrishnan; Pawar, Sayali; Dadwal, Arun; Joy, Pattayil Alias; Mukherjee, Shatabdi Porel (ChemistrySelect, 2019)
Superparamagnetic cobalt ferrite (CFO) nanocrystals (NCs) with sizes similar to 6 nm and similar to 4 nm were synthesized using a facile solvothermal method using fatty acids, lauric acid and stearic acid, as the capping agents. The synthesized nanocrystals were well characterized by XRD, FT-IR, XPS, SEM and TEM. The formation mechanism was explored and it was shown that the fatty acid was actually chemisorbed as a carboxylate onto the surface of CFO NCs. The experimental results specify that the size and size distribution of the CFO NCs were highly dependent on the length of fatty acid hydrophobic chain. Corresponding changes of the magnetic properties were investigated by measuring magnetization as a function of field and temperature, which suggest that the CFO NCs were superparamagnetic in nature. The catalytic properties for the oxidation of styrene in organic medium were examined by using the synthesized CFO NCs with sizes similar to 6 nm and similar to 4 nm. The synthesized CFO NCs, well dispersible in organic media, were demonstrated to be highly catalytically active, reached 100% conversion of styrene in 12 h with similar to 77% and similar to 82% selectivity for styrene oxide respectively. The magnetic CFO nanocatalysts were easily separated and recovered from the reaction medium by an external magnet, and reused for several cycles without losing catalytic selectivity for styrene oxide.
Keywords: Cobalt ferrite; epoxidation; Fatty acids; magnetic properties; nanocrystals